2023
DOI: 10.3389/fanim.2023.1218175
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and phenotypic time trends of litter size, piglet mortality, and birth weight in pigs

Abstract: IntroductionLitter size in pigs has increased steadily since 1990. Because of unfavorable genetic correlations with piglet mortality, breeding goals should include survival traits next to litter size. Unbalanced breeding programs that neglect this requirement have produced increased mortality levels, attracting negative public attention. Balanced breeding does not have this disadvantage, but the general public is largely unaware of this.MethodsWe present long-term time trends as realized in commercial breeding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 90 publications
(100 reference statements)
0
6
0
Order By: Relevance
“…However, the selection for more uniform litters can have negative impacts both on the litter size and/or on the mean weight of the piglets [23,24]. Increased litter size has been a goal of genetic selection progress in the last decades and, according to recent evaluations, it can continue to be a strategic goal in pig genetic improvement programs because the negative effects on preweaning mortality of piglets can be controlled [1]. The possible negative impacts on the mean weight of the piglets can be also problematic because lighter piglets have low survival rates [28][29][30] and, due to the positive relationship between birth weight and weaning weight [30][31][32], piglets could be weaned with less body weight, resulting in augmented difficulties to cope the weaning transaction challenges [33,34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the selection for more uniform litters can have negative impacts both on the litter size and/or on the mean weight of the piglets [23,24]. Increased litter size has been a goal of genetic selection progress in the last decades and, according to recent evaluations, it can continue to be a strategic goal in pig genetic improvement programs because the negative effects on preweaning mortality of piglets can be controlled [1]. The possible negative impacts on the mean weight of the piglets can be also problematic because lighter piglets have low survival rates [28][29][30] and, due to the positive relationship between birth weight and weaning weight [30][31][32], piglets could be weaned with less body weight, resulting in augmented difficulties to cope the weaning transaction challenges [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…The number of weaned piglets per year is a key indicator in swine breeding, determining its profitability. During the last decades, genetic selection has led to a significant litter size increase [1]. However, larger litters are associated with higher piglet pre-weaning mortality [2][3][4] which is a major problem in commercial pig production, both from an economic and welfare point of view [5].…”
Section: Introductionmentioning
confidence: 99%
“…Adopting the second stage slowed or even reversed the decline of fitness traits that were part of the selection index ( Brito et al, 2021 ). Multi-trait selection became common in pigs ( Knap, 2022 ; Knap et al, 2023 ) and chickens ( Neeteson et al, 2023 ), which reversed the decline of many traits. While many traits can be easily recorded, some traits are difficult to measure, creating a possibility of a decline.…”
Section: Second Stage—selection For Production and An Increasing Numb...mentioning
confidence: 99%
“… Cheverud (1984) showed that improving two traits was five times faster when the genetic correlation was 0 instead of −0.8. In a pig breeding scheme, where the number of piglets born is negatively correlated (unfavorable) with birth weight, it took 9 yr of balanced selection under GS to increase both traits by 2.8 piglets/litter and 0.27 kg, respectively, while reducing the number of stillborn piglets by 0.53 ( Knap et al, 2023 ). Thus, progress can be made in a well-designed breeding program, although it may be slow.…”
Section: Mitigating the Negative Effects Of Gsmentioning
confidence: 99%
“…In production animals, selective breeding has resulted in a tremendous increase in e.g. milk production of dairy cattle (NAV trends, 2023;Oltenacu and Broom, 2010), litter size in pigs (Knap et al, 2023), and improved growth rate in fish (Gjedrem and Robinson, 2014). Selective breeding of insects has not been widely implemented yet.…”
Section: Introductionmentioning
confidence: 99%